Optimization of linear objective function subject to Fuzzy relation inequalities constraints with max-product composition - Shivanian, Elyas; Khorram, Esmaile (Iranian journal of fuzzy systems (Online), 2010)
In this paper, we study the finitely many constraints of the fuzzy relation inequality problem and optimize the linear objective function on the region defined by the fuzzy max-product operator. Simplification operations have been given to accelerate the resolution of the problem by removing the components having no effect on the solution process. Also, an algorithm and some numerical and applied examples are presented to abbreviate and illustrate the steps of the problem resolution.